Ellagic Acid Protects Cardiac Arrhythmias Following Global Cerebral Ischemia/Reperfusion Model: - Hoseiny Nejad, Khojasteh; Dianat, Mahin; Sarkaki, Alireza; Farbood, Yaghoub; Badavi, Mohammad; Gharib-Naseri, Mohammad Kazem (Galen Medical Journal, 2019)
Background: Cerebral ischemia/reperfusion (I/R) could increase the reactive oxidative stress in the cardiomyocytes. Also, some studies report cardiac arrhythmias following oxidative stressor such as I/R. Hence, this study was aimed to investigate the effects of ellagic acid (EA) against arrhythmias in a cerebral I/R model. Materials and Methods: Thirty-two male rats were randomly allocated into four groups: Sham (normal saline, 10 days), EA (100 mg/kg EA, 10 days), I/R (20 min ischemia followed by 30 min reperfusion, 10 days), and EA + I/R (100 mg/kg EA before I/R). In all animals, electrocardiogram (ECG) was recorded pre-ischemia and postischemia on the first and 11th days, respectively. Results: The I/R group showed an abnormally prolonged QTc interval after ischemia compared to the preischemia and control groups. EA administration in the EA+I/R group significantly reduced this prolonged QTc interval (P< 0.01). In the I/R group, ischemic/reperfusion resulted in a prolonged QRS complex and an elevated ST, which EA significantly prevented (P<0.01). In addition, EA significantly prevented the dramatically shortened RR interval induced by reperfusion (P<0.01). The incidence of ventricular fibrillation significantly increased in the I/R group; then it dramatically decreased following the administration of EA (P<0.0001). Conclusion: EA pretreatment repaired the adverse effects of I/R on the ECG parameters, which can be attributed to its negative chronotropic effects. EA pretreatment can prevent the cerebral I/R-induced heart arrhythmias. [GMJ.2019;8:e1235]